Influence of flow on phosphorus-dynamics and particle size in agricultural drainage ditch sediments. - Jay Capasso; Jehangir H Bhadha; Allan Bacon; Lilit Vardanyan; Raju Khatiwada; Julio Pachon; Mark Clark; Timothy Lang (PLoS ONE)
Particle size is one factor affecting phosphorus (P) dynamics in soils and sediments. This study investigated how flow facilitated by hydraulic pumps and aquatic vegetation species water lettuce (Pistia stratiotes) and water hyacinth (Eichhornia crassipes) affected particle size and P-dynamics in organic sediments in agricultural drainage ditches. Sediments with finer particle size (>0.002 mm) were hypothesized to contain greater total P (TP) and less labile P than sediments with coarser particle size. Particle size was determined using a LS 13 320 Laser Diffraction Particle Size Analyzer. Sediments were tested for pH, TP, and organic matter. Fractions of P were determined using a sequential fractionation experiment and 31P Nuclear Magnetic Resonance (NMR) Spectroscopy. Larger average particle size and lower average total P concentrations were found in the inflows of the field ditches compared to the outflows. Presence of flow and aquatic vegetation did not have a significant impact on particle size, TP, or labile P fractions. Median (p = 0.10) particle size was not significantly correlated to TP. Overall, there was an average trend of coarser particle size and lower P concentrations in the inflow compared to the outflow. The presence of inorganic limerock could have affected results due to increased P adsorption capacity and larger average particle size compared to the organic fraction of the sediment.